Philosophy of liberation - signs of decoloniality in Dussel (Research, Society and Development, 2020)
This article has a purpose to identify the signs of decoloniality at work ‘Philosophy of Liberation’ by Enrique Dussel, where it is proposed a liberating philosophical practice of a colonial epistemic thinking and of doing, starting from the praxis and having as material foundation human life. Therefore, we use the bibliographic research of relevant works to the thematic approach. That way, we interpret the European philosophizing and Latin American to organize these ideas. We consider that the philosophical discourse of liberation leans to a practical experience that originates from a concrete reality, in order to evidence projects andtransformation programs daily. When proposing this doing philosophical that takes as a reference the human praxis, Dussel, shows the premises of decolonial discourse, that even if it is a current concept had been properly treated and experienced as liberation from all victimization and denial of every paradigmatic formula that denies life.